Sedum pallidum (Crassulaceae) – чужорідний вид флори рівнинної частини України - Shynder, O.I.; Negrash, Y.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
The objective of this study was to evaluate the current distribution of Sedum pallidum in Ukraine, to analyze its state in the alien flora of Ukraine. Material and methods. The studies were conducted in 2008–2019 in the plain part of Ukraine and the Crimean Mountains. Literature information, several national herbarium collections, and other sources were analyzed. Special attention was paid to the delimitation of synanthropic locations of S. pallidum from cultural ones. Results. S. pallidum is a sub-euxine species, which range occupies the Crimean Mountains. It is widely cultivated throughout Ukraine and is prone to naturalization, thanks to its vegetative and generative reproduction. In general, about 30 synanthropic locations of S. pallidum have been recorded, mainly in the Middle Prydniprovia and Western Ukraine. Urban lawns and roadsides on light substrates are favorable ecological niches for S. pallidum. Соnclusions. S. pallidum is the alien species in the flora of the plain part of Ukraine and ergasiophyte in its origin. A potential secondary synanthropic range of this species occupies the whole country except the Carpathian highlands. It has been established that S. pallidum in the culture of the Forest-Steppe is a perennial herb. Two races identified in its composition (var. pallidum and var. bithynicum) are probably ecads and have no systematic importance. In the culture, S. pallidum is characterized by successful vegetative and generative reproduction, which contributes to its naturalization. S. pallidum is often confused with other species of the genus, which does not contribute to its study in adventive floras. A key for S. pallidum determination has been proposed.